Remediation technologies for oil contaminated soil - M. Mambwe; K. Kalebaila; T. Johnson (Global Journal of Environmental Science and Management)
Crude oil continues to impact many nations as it is among the major sources of fuel.  Its role in making life in modern societies comfortable cannot be overemphasized as it is readily available and easy to use. Contamination resulting from its use in industries such as mining, transportation and petroleum especially soil contamination cannot be overlooked. Soil pollution resulting from oil contamination can be seen as being among the twenty-first-century vulnerabilities because if not well taken care of the consequences can be devastating. Soil contamination is of interest in most societies because it affects both the environment and humans. This review highlights common sources of soil pollution and their effects, oil waste disposal methods, soil remediation techniques that are well established and those still in their infancy. Such techniques include bioremediation such as phytoremediation and landfarming, where percent removal of contaminated soils was reported from 68% to 89 % in 40 days to 1 year, respectively; physical methods such as excavation and incineration (75-86% removal); chemical methods such as oxidation (48 % by Fenton process); and photocatalysis (67% using titanium dioxide). The choice of remediation in mining, transportation and petroleum industries depends on the urgency and hazardous effects of the pollutant. In Zambia, Mopani Copper Mines uses landfarming as a means to mitigate large amounts of soil contaminated with oil wastes, but the process is slow. In the proposed research, photocatalysis coupled with adsorption of oil on clay will be used to assess the effectiveness of this emerging technology to quicken the degradation of oil in soils. Clay will be incorporated with metal ions and with hydrophobic groups to enhance light absorption and oil-clay interaction, respectively. Photochemical remediation techniques for remediation of soils polluted with oil have attracted considerable interest as the processes are reported to enhance the degradation of oils in soil compared to the biological and physical methods. The extent of photo-degradation of oil waste will be evaluated using the Soxhlet technique by determining the percent residual oil. The importance of remediating contaminated soil in any nation cannot be overemphasized as consequences of not remediating this precious resource might be devastating. Since economic development through industrialization will continue, there is need to constantly improve on methods of mitigating the impact of wastes on the environment, especially in developing countries, where engineering of cheap, nontoxic materials for soil remediation is paramount. ========================================================================================== COPYRIGHTS©2021 The author(s). This is an open access article distributed under the terms of the Creative Commons Attribution (CC BY 4.0), which permits unrestricted use, distribution, and reproduction in any medium, as long as the original authors and source are cited. No permission is required from the authors or the publishers. ==========================================================================================